Somarasa : Spirituous Drinks in Ancient India - Thapliyal, Uma Prasad, (Brill | Manohar Publishers & Distributors, 2024)
Indians have been drinking some form of wine for the past four thousand years. In spite of it, a kind of pretence pervades the society against drinking of wine. In the Vedic times, Somarasa and Surā were much in common use. Indra, the Vedic deity of war, greatly relished it, and not unoften got inebriated. Interestingly, the ninth book of the Rgveda is fully devoted to Soma, its preparation and use. Similarly, later works like Astādhyāyi, Rāmāya]na, Mahābhārata, Arthaśāstra, Raghuvamśa, Harsacarita, etc. also refer to the popularity of wine among all sections of the society. Dharmaśāstras, however, occasionally speak against the use of wine by the Brāhmanas. Perhaps, the book may help in correcting our hypocritic attitude against wine though abstinence from alcoholic drinks is always beneficial.